Existence of Dissolved Oxygen near Anode Catalyst in Proton Exchange Membrane Water Electrolyzers. Issue 4 (1st April 2022) - Watanabe, Konosuke; Wakuda, Kohei; Wani, Kodai; Araki, Takuto; Nagasawa, Kensaku; Mitsushima, Shigenori
Abstract : The anode mass transport loss is one of the issues to expand the practical application scope of proton exchange membrane water electrolyzers (PEMWEs). However, there are few reports concerning the oxygen transport inside and near the anode catalyst layer (CL). Although especially near the anode CL, there are two transport mechanisms: gaseous oxygen and dissolved oxygen, there are no reports, as far as we could find, that experimentally examined the existence of dissolved oxygen in PEMWE. Herein, the bubble growth behavior near the anode catalyst was observed using a high-speed camera, and the bubble radius change was investigated. The radii of the bubbles continued to increase after they left the anode catalyst layer surface, and the existence of dissolved oxygen and the formation of an oxygen supersaturated region were confirmed. The existence of dissolved oxygen is an important factor in the future evaluation of anode mass transport loss in PEMWE and a good revelation for the future development of the anode porous structure to reduce the anode mass transport loss.